Spectrum of Dyselectrolytemia Induced by Liposomal Amphotericin B In Neonates - Mughal, Asif Rasool; Tabussam, Samina; Maqsood, Ali; Hamid, Faqeeha; Rehman, Jawad ur; Munawar, Bilal (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the spectrum of dyselectrolytemia induced after treatment by liposomal Amphotericin B (LAmB) in neonates being treated for fungal infectionsStudy Design: Quasi-experimental studyPlace and Duration of Study: Department of Pediatrics, Combined Military Hospital Rawalpindi, Pakistan from Aug 2023 to Jan 2024Methodology: Pre-therapy baseline investigations including Blood complete picture, Urine RE and serum electrolytes (Na, K, Ca, Mg, PO4) were sent baseline values were recorded. LAmB therapy was initiated in all patients at a dose of 4 mg/kg/day for a total of 14 days. Primary variables studied were changes in serum sodium, potassium, calcium, magnesium, phosphate, and for glycosuria before starting and after completion of therapy.Results: When comparing the primary variables before and after LAmB treatment, mean levels of sodium were 140.77±0.99 MEq/L before therapy versus 132.16±1.05 MEq/L after therapy (p